CONGENITAL HYPOFIBRINOGENEMIA; AN UNEXPECTED CULPRIT OF BLINDNESS IN AN INFANT - Ubaid, Aamer; Waheed, Farishta; Waheed, Saadia; Shafqat, Madeeha (Journal of Ayub Medical College Abbottabad, 2020)
Background: Congenital hypofibrinogenemia is a rare haematological disorder in which the production of functional fibrinogen is impaired because of the inherited mutation. Hypofibrinogenemia affects the coagulation cascade leading to bleeding diathesis and one of its manifestations can be recurrent Vitreous haemorrhages, sometimes leading to irreversible loss of vision. Therefore, Hypofibrinogenemia must be included in the differential diagnosis of Vitreous haemorrhage, particularly in young children. We report a case of a four months old female infant who was brought by her mother to the unit since she was afraid that the child might be unable to see since she was not following things for the last one month. Her ophthalmologic examination revealed bilateral vitreous haemorrhages. Further workup for the cause of the bleeding confirmed the diagnosis of hypofibrinogenemia which was then managed accordingly. Keywords: Fibrinogen; Hypofibrinogenemia; Missense mutation